2015
DOI: 10.1002/stem.1966
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the Mucocutaneous Manifestations by Human Cord Blood Derived Nonhematopoietic Stem Cells in a Mouse Model of Recessive Dystrophic Epidermolysis Bullosa

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a severe skin blistering disease caused by mutations in COL7A1-encoding type VII collagen (C7). Currently, there is no curative therapy for patients with RDEB. Our previous studies demonstrated that human umbilical cord blood (HUCB) derived unrestricted somatic stem cells (USSCs) express C7 and facilitate wound healing in a murine wounding model. The primary objective of this study is to investigate the therapeutic functions of USSCs in the C7 null (Col7a1 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…Furthermore, compared to other sources for stem cell therapy such as bone marrow cells for CNS therapy, USSCs showed lower immunogenicity, possibly enabling them to cross an intact BBB. USSCs have the ability to migrate to the wound or injury; they express many chemokine receptors such as CXCL12 (for SDF1), PDGFR (for HMGB1), and CCR2 (for CCL7), [31] which might direct their specific migration to the site of injury. It is also important to mention that the localization of USSCs in the brain after IV injection is not randomly dispersed; it follows a trajectory path.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compared to other sources for stem cell therapy such as bone marrow cells for CNS therapy, USSCs showed lower immunogenicity, possibly enabling them to cross an intact BBB. USSCs have the ability to migrate to the wound or injury; they express many chemokine receptors such as CXCL12 (for SDF1), PDGFR (for HMGB1), and CCR2 (for CCL7), [31] which might direct their specific migration to the site of injury. It is also important to mention that the localization of USSCs in the brain after IV injection is not randomly dispersed; it follows a trajectory path.…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] In previous studies, our group engineered USSCs to express the luciferase reporter gene, confirmed a stable nonteratogenic phenotype, and then successfully tracked USSC migration in a living animal model of recessive dystrophic epidermolysis bullosa (RDEB) and in excisional wounding healing. [24,31] In the RDEB model, USSC administration migrated to the site of injury and suppressed TGFβ signalingmediated fibrosis and attenuated inflammatory cytokine expression (IL6, IFNγ, and IL17α). [32] The goal of the present pilot study was to investigate the therapeutic potential of USSCs in a premature rabbit pup model of glycerol-induced IVH.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that following intrahepatic ( i.h. ) administration in neonatal col7a1 −/− mice, USSCs disseminated into the circulation and migrated to skin and intestines . Specifically, USSCs were identified in the dermis within a week and in the hair follicles within 2 weeks of administration.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies from the research team of Govindaiah Vinukonda (New York Medical College, Valhalla, New York, USA) explored engineered human cord blood USSCs as a therapy for recessive dystrophic epidermolysis bullosa, an inherited disease majorly affecting the skin . In their new Stem Cells Translational Medicine article, Vinukonda et al sought to extend this approach to the treatment of IVH, a severe complication of preterm birth that leads to hydrocephalus, cerebral palsy, and mental retardation through assessments in a rabbit disease model.…”
Section: Featured Articlesmentioning
confidence: 99%